'Lacking' subjects: Challenging the construction of the 'empowered' graduate in museum, gallery and heritage studies. (April 2023) - Coffield, Emma; Markham, Katie; Crosby, Jessica; Athanassiou, Maria; Stenbom, Cecilia
This article challenges what is now a common assumption in Higher Education; that teaching for employability will result in enabled and empowered graduates. Drawing upon empirical data, and Foucault's concept of subjectification, we argue that discourses of employability instead encouraged museum, gallery and heritage postgraduate students at one UK-based institution to perceive themselves as subjects 'lacking' the resources needed for work – an understanding of self that formed prior to study, which then permeated the entire learning and teaching experience. Moreover, we note that the trajectory from 'lacking student' to 'employable graduate' is often reliant upon an accrual of assets (e.g. work experience, skills) not openly available to all. As such, the article sounds a note of caution with regards the rhetoric of employability within Higher Education, while giving voice to students' perspectives and anxieties around employability.